Dynamic Role of Indonesian Islamic Banks in Increasing Economic Growth in Indonesia (Analysis of Opportunities and Obstacles of Islamic Banks After Merger) (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The role of the Islamic economy as one of the sources of Indonesia's new economic growth requires the integration of every element of the Islamic economy which is reflected in a strong Islamic economic ecosystem. This momentum is utilized by the Government of Indonesia to increase the role of Islamic economics and finance in the national economy. The merger of three Islamic banks Bank Syariah Mandiri, Bank BRI Syariah, and Bank BNI Syariah into Bank Syariah Indonesia (BSI) is expected to have an impact on strengthening economic growth in Indonesia. This study aims to determine the role of Bank Syariah Indonesia (BSI) on economic growth in Indonesia after the merger analysis of opportunities and obstacles. The research used a qualitative approach with a field study research design. Data collection techniques were carried out by analyzing interviews and documentation. The results of the study state that the opportunities for Bank Syariah Indonesia in the future are very large. Given, there are many components that support the creation of healthy and reliable Islamic banking. However, the opportunity to become an established Islamic banking cannot be separated from various challenges. Both those that come from within, and those that come from outside. The role of the economy is related to economic growth caused by the development of capital and funds from Bank Syariah Indonesia which is able to increase financing in business and national development. Bank Syariah Indonesia has consolidated assets from the merger of Rp239.56 trillion, making it the largest Islamic bank in Indonesia. The strength of Bank Syariah Indonesia's assets also includes intangible assets such as reputation, network, human capital, and management.
Keywords: Merger; Bank Syariah Indonesia; Opportunities; Barriers; Economic Growth